A Comprehensive Evaluation of RPL under Mobility. (12th March 2012) - Lee, Kevin C.; Sudhaakar, Raghuram; Ning, Jianxia; Dai, Lillian; Addepalli, Sateesh; Vasseur, J. P.; Gerla, Mario
Abstract : This paper focuses on routing for vehicles getting access to infrastructure either directly or via multiple hops through other vehicles. We study routing protocol for low-power and lossy networks (RPL), a tree-based routing protocol designed for sensor networks. Many design elements from RPL are transferable to the vehicular environment. We provide a simulation performance study of RPL and RPL tuning in VANETs. More specifically, we seek to study the impact of RPL's various parameters and external factors (e.g., various timers and speeds) on its performance and obtain insights on RPL tuning for its use in VANETs. We then fine tune RPL and obtain performance gain over existing RPL.